Determinan Nilai Perusahaan pada Sub Sektor Perbankan: Bukti Empiris dari Kepemilikan Institusional, Kebijakan Hutang, Pertumbuhan, Cash Holding, Inflasi, dan Suku Bunga - Ilham Aidil Putra; Faiza Muklis (Al-Manar Journal of Economic and Social Studies, 2025)
This study aims to analyze the influence of institutional ownership, debt policy, firm growth, cash holding, inflation, and interest rates on firm value in banking sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. This research employs a quantitative approach using secondary data obtained from banking companies’ financial statements and Bank Indonesia (BI) reports. The research sample was selected using a purposive sampling technique, resulting in a total of 164 observations. Data analysis was conducted using classical assumption tests and panel data regression analysis. The findings indicate that cash holding has a positive effect on firm value. High cash holding increases firm value by providing financial flexibility to seize investment opportunities without relying on external financing. Additionally, strong cash reserves send a positive signal to investors that the company is financially healthy and capable of withstanding future risks. Meanwhile, institutional ownership, debt policy, firm growth, inflation, and interest rates were found to have no significant effect on firm value.